ANALISIS POTENSI KONVERSI ENERGI SUNGAI TOLADAN BERDASARKAN DEBIT ANDALAN UNTUK PEMBANGKIT LISTRIK TENAGA MIKROHIDRO - Agnes Julia Kopeuw ,; Sakka Irawan,; Melissa Aeudia Daullu, (Journal of Innovation Research and Knowledge, 2025)
The Toladan River, located in Jayapura Regency, Papua, offers promising opportunities for renewable energy development, particularly small-scale micro-hydropower systems. Accurate estimation of dependable flow is essential for determining hydropower feasibility and sustainable energy planning. This study analyzes the dependable flows of the Toladan River using field-based discharge measurements from three observation points and employing a flow-duration-curve (FDC) statistical approach. Discharge measurements were obtained using the float method, supported by cross-sectional geometry assessments at each site. Results show that average discharges at the three observation points were 0.382 m³/s, 0.448 m³/s, and 0.654 m³/s, respectively, reflecting significant variations in channel dimensions. These values were statistically processed to estimate dependable flow rates at exceedance levels of Q50, Q70, and Q90. The analysis indicates that Q90 dependable discharge remains adequate for small-scale micro-hydropower development. Overall, this study demonstrates that the Toladan River provides a stable flow regime conducive to micro-hydropower generation, offering essential baseline data to support renewable energy planning in Papua